To dance : a memoir - Siegel, Siena Cherson (Atheneum Books for Young Readers, 2006)
The author describes how she first decided she wanted to be a ballerina at the age of six, and how that dream carried her from her home in Puerto Rico to dance class in Boston to performing with the New York City Ballet